Coordination Of Stakeholder In The Implementation Of Non-Cash Food Assistance Program At The Social Services Agency - Yayat Sudrajat; Indra Kristian (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
Poverty is a condition of economic inability to fulfill the average standard of living of people in an area. One of the programmes established by the government to reduce the burden on the community in fulfilling basic needs is the Non-Cash Food Assistance Programme (BPNT). The implementation of the BPNT programme at the Regency/Region level is under the control of the Subang Regency Social Service, which is part of the Food Social Assistance Coordination Team and is supported by other government agencies and departments. Coordination is key in supporting the success of a programme. The basic mechanisms in achieving coordination are the vital components of management, namely managerial hierarchy, rules and procedures and the establishment of plans and objectives. The purpose of this research is to describe the role and function of stakeholder coordination as well as obstacles or barriers to coordination between relevant stakeholders in the implementation of the Non-Cash Food Assistance Programme (BPNT) in Subang District. The results of this study show that aspects of the managerial hierarchy have been carried out, rules and procedures have been implemented and the determination of plans and objectives has been prepared since the start of activity planning, but the results are still not optimal.